Self-Efficacy and Social Support as Predictors of Entrepreneurial Intention with Entrepreneurial Motivation as a Mediator - Andika Isma; Salim Diarra (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2025)
High unemployment rates in Indonesia necessitate creative solutions, with entrepreneurship being a key driver of job creation. University students, as prospective graduates, have a crucial role to play in this endeavor. This study investigates the influence of self-efficacy and social support on entrepreneurial intention among students, with entrepreneurial motivation as a mediating variable. Employing a quantitative approach with an explanatory descriptive design, the study population comprised all students (128) in the 2023 Entrepreneurship Study Program at the Faculty of Economics and Business, Universitas Negeri Makassar. A sample of 118 students was selected through proportional random sampling. Data were collected using an online questionnaire via Google Form and analyzed using SPSS version 27. The results indicate that self-efficacy significantly influences entrepreneurial motivation but not entrepreneurial intention directly. Social support did not significantly influence either entrepreneurial intention or motivation. Entrepreneurial motivation significantly influenced entrepreneurial intention. Furthermore, self-efficacy had a significant indirect effect on entrepreneurial intention through entrepreneurial motivation, while social support did not.